BUDAYA BAHARI DAM TRADISI NELAYAN DI INDONESIA - Yunandar, Yunandar (Fakultas Ilmu Budaya Universitas Diponegoro, 2006)
There are at least five phenomena which mark the complexity of maritime culture and fisherman tradition in Indonesia; social group of the maritime society, the development of economic sectors concerning sea products, social hierarchy in the daily maritime activities, the relationship between the elements of maritime culture and life sectors of the society, and the continuation and alteration of maritime culture's elements. In order to acquire a deep study on the complexity of maritime culture, there are several concepts used in this paper: Koentjaraningrat's concept of